2015
DOI: 10.1038/sj.bdj.2015.594
|View full text |Cite
|
Sign up to set email alerts
|

Perception of studying dental law and ethics among postgraduate dental students in the UK

Abstract: Law and ethics is an integral part of medical and dental professional practice. The subject is touched upon in the undergraduate curriculum. Historically, dentists interested in postgraduate study in this subject have accessed courses on medical law and ethics. While there are areas of shared interest (for example, consent, confidentiality) there are differences in emphasis and content (for example, end of life care, organ transplants, etc) which are not relevant to dentistry. A new postgraduate certificate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Those working in General Dentistry and Aesthetics Dentistry are more knowledgeable about aspects of the section on ethics. 4. No signi cant correlation was found between the amount of time spent on the job and the degree of knowledge of the subject.…”
Section: Discussionmentioning
confidence: 89%
“…Those working in General Dentistry and Aesthetics Dentistry are more knowledgeable about aspects of the section on ethics. 4. No signi cant correlation was found between the amount of time spent on the job and the degree of knowledge of the subject.…”
Section: Discussionmentioning
confidence: 89%
“…14 Graduates generally acknowledge their need for ethical reinforcement when starting practice independently. 15 Moreover, studies have shown that knowledge of ethics can follow a downward trend over time. 16 Hence, it is necessary to review the same ethical topics in postgraduate programs.…”
Section: Discussionmentioning
confidence: 99%
“…They have limited abilities to integrate and use the information in clinical practice due to their inexperience in clinical encounters with ethical topics in predoctoral training 14 . Graduates generally acknowledge their need for ethical reinforcement when starting practice independently 15 . Moreover, studies have shown that knowledge of ethics can follow a downward trend over time 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and assessing ethical dental practice is a challenge, and students find that ethics is a more challenging as a topic compared to studying dental law. Research showed that PG dental students find studying ethics challenging 3,4 , since studying a multifaceted subject like ethics requires a great deal of thinking and reflection. Dentists with an empirical science background come to the social science of ethics with its own distinctive language, traditions and apparent imprecisions with a mixture of unease, excitement and some confusion.…”
Section: Teaching Dental Law and Ethicsmentioning
confidence: 99%